How platforms transform banking business models : The context of open banking in Europe - Leskinen, Tiina (My University, 2022)
European open banking initiative, the Revised Payment Services Directive (PSD2), offers a unique legal context that enables financial institutions and other licensed third-party providers to deliver customers financial services that are based on customer account data in another bank. This is done via open application programming interfaces that are a technical realization of platforms. The objective of this study is to analyze how platforms affect the banking business models in the context of open banking in Europe. The sub-questions are to find out how external drivers impact banks’ adoption of more open business models, how platforms change the banking competition, and what kind of platform business models banks could adopt. Based on the findings of the existing literature a framework is built to consider the impact of the unprecedented combination of new open banking regulatory requirements, Fintech and large technology companies, changing consumer behavior and expectations, and platformization to the banking business models. Four broad options for bank’s open banking business models are presented based on the added value to the proposition of the bank and the level of openness of the business model. The empirical study was conducted as a qualitative research and data collected using semi-structured expert interviews which were based on the theoretical framework. Also, podcasts were used as secondary data. The qualitative data was analyzed and processed using thematic analysis. The empirical research findings largely support the existing literature but provide also new insights on the external factors impacting banks’ business model transformation, emphasizing particularly partnership management skills and the co-development with third parties. When incumbent banks adapt to the external changes, they face the challenge of incrementally transforming and digitizing their traditional pipeline business model as well as simultaneously creating new more open platform business models parallel to the existing one. It appears evident that all presented four open banking business models entail some rethinking of the traditional banking business models – rethinking of value proposition from bank and nonbank players, value delivery through new interfaces and channels of contact, value creation via external cooperation as well as value capture in changing revenue models and profit allocation.

Euroopan Unionin toinen maksupalveludirektiivi (PSD2) avaa kolmansille osapuolille (pankeille tai muille maksupalveluntarjoajille) rajapinnan kautta pääsyn asiakkaan tiliin ja tilitietoihin mahdollistaen uusien tai vaihtoehtoisten palveluiden tarjoamisen asiakkaan antaessa tähän luvan. PSD2 on esimerkki uudesta avoimen pankkitoiminnan maailmasta, joka perustuu avoimiin rajapintoihin ja alustaliiketoimintamalleihin. Tämän tutkimuksen tavoitteena on analysoida, miten alustat vaikuttavat pankkien liiketoimintamalleihin avoimen pankkitoiminnan yhteydessä Euroopassa. Alakysymyksissä keskitytään siihen, miten ulkoiset tekijät vaikuttavat pankkien avoimempien liiketoimintamallien omaksumiseen, miten alustat muuttavat kilpailua pankkialalla, ja millaisia alustaliiketoimintamalleja pankit voisivat omaksua. Teoreettisessa viitekehyksessä otetaan huomioon ennen näkemätön yhdistelmä avoimen pankkitoiminnan sääntelyvaatimuksista, uusista yrityksistä ja suurista teknologia yhtiöistä, muuttuvasta kuluttajakäyttäytymisestä sekä tämän kokonaisuuden vaikutuksista pankkien liiketoimintamalleihin. Pankkien avoimen pankkitoiminnan liiketoimintamalleille esitetään neljä vaihtoehtoa niiden tuoman arvon ja liiketoimintamallin avoimuuden tason perusteella. Empiirinen tutkimus toteutettiin kvalitatiivisena tutkimuksena ja aineisto kerättiin teoreettisen viitekehyksen pohjalta puolistrukturoiduilla asiantuntijahaastatteluilla. Myös podcasteja käytettiin toissijaisena datana. Laadulliset tiedot analysoitiin temaattisella analyysillä. Empiiriset tutkimustulokset tukevat pitkälti olemassa olevaa kirjallisuutta, mutta toivat esiin myös uusia näkemyksiä pankkien liiketoimintamallien muutokseen vaikuttavista ulkoisista tekijöistä korostaen erityisesti kumppanuusjohtamistaitoja ja yhteiskehitystä kolmansien osapuolten kanssa. Kun vakiintuneet pankit sopeutuvat ulkoisiin muutoksiin, niiden haasteena on asteittain muuttaa ja digitalisoida perinteistä putkiliiketoimintamalliaan sekä samanaikaisesti luoda uusia avoimemman alustan liiketoimintamalleja nykyisen rinnalle. Voidaan päätellä, että kaikki tutkimuksessa esitellyt neljä avointa pankkitoimintamallia edellyttävät perinteisen liiketoimintamallin uudelleenajattelua – osapuolten arvoehdotuksen näkökulmasta, arvon tuottamisessa uusien rajapintojen ja kanavien kautta, arvon luomisessa myös ulkoisen yhteistyön kautta sekä arvon saamisessa muuttuvissa ansaintamalleissa.
Keywords: business model, business model transformation, open business model, platform business model, open banking